The hurricane wars : a novel [large type] - Guanzon, Thea (Guanzon, Thea. Hurricane wars, 2023)
"The heart is a battlefield. War has raged for a decade in Lir, and orphaned soldier Talasyn has learned to keep her powers hidden to survive. As the last known Lightweaver on the continent, she can create radiant weapons that cut through the invading Shadowforged warriors' dark magic. But all that changes when she is forced to reveal her abilities on the battlefield to defend herself from the Shadowforged prince himself, Alaric Ossinast. In a clash of light and dark, their magic combines to create a new force the likes of which has never been seen. This rare power could be the key to saving many lives-if Talasyn and Alaric don't destroy each other first. Pushed together into a fraught political engagement, the two adversaries find themselves pawns in a much bigger game between conflicting nations. Neither is pleased by the arrangement, but when a new threat emerges, necessity forces the pair to confront the secrets at the heart of the war and find, in each other, a searing passion-one that could save their world, or end it. An exquisite fantasy brimming with unforgettable characters, sizzling romance, and richly drawn worlds, The Hurricane Wars marks the breathtaking debut of an extraordinary new writer"--